EKSTRAKURIKULER “TARI PESISIR” SEBAGAI STRATEGI PENANAMAN PERCAYA DIRI PESERTA DIDIK MIS HIDAYATUL MUHAJIRIN PALANGKA RAYA - Istiyati Mahmudah; Muhibah Amaliyah; Fitriani Fitriani; Dwi Ayu Lestari (JURNAL IMAJINASI, 2023)
This study aims to find out the strategies for instilling confidence in MIS Hidayatul Muhajirin Palangka Raya students through the extracurricular "Coastal Dance". The implementation method in this study uses field research that is descriptive qualitative in nature. The analysis techniques are field observations, interviews, and documentation. The results in this study are that the trainer applies three methods, namely: the peer tutor method, the demonstration method, and the exploration method. Through the application of this method students can appear confident, gain friendships, get additional extracurricular value on report cards and provide special awards for madrasas from competition activities participated by students in these extracurriculars. The supporting factors for the implementation of these extracurricular activities are 1) Student Interests, 2) Facilities and Infrastructure. While the inhibiting factor is that the costumes used to participate in the competition activities have not changed compared to the costumes used before.